The Influence of Packing Design and Product Innovation on Customer Purchase Decisions, the Intervening Role of Marketing Strategy - Diah Dwi Ayuni; Bayu Kurniawan; Noventia Karina Putri (Dinasti Review Publisher, 2026)
Background: Taiwan is famous for its rich tea culture, but tea producers in Yunlin County face a challenge in attracting the younger generation, especially students who have modern tastes. While attractive Packaging Design and creative Product Innovation are important to grab attention, these factors often need a strong Marketing Strategy to actually convince university students to buy the product. This research aims to explore how marketing serves as a bridge (intervening role) between design and innovation to successfully influence the Purchase Decisions of students. Objective: This study aims to examine the influence of packaging design and product innovation on consumer purchase decisions for tea (茶 / Chá), with marketing strategy as an intervening variable. Methods: This quantitative study uses surveys to collect data from university students. Using SPSS, it analyzes how Packaging Design and Product Innovation (independent variables) influence Purchase Decisions (dependent variable), with Marketing Strategy serving as the intervening variable sample:The participants are university students selected through purposive sampling. This study focuses on active students who have experience with or an interest in tea consumption to understand their buying behavior. Key Findings: The findings show that Packaging Design and Product Innovation significantly boost Purchase Decisions. Specifically, Marketing Strategy acts as a key bridge, making the design and innovation much more effective in convincing university students to buy the tea products. Conclusion & Implications: Marketing Strategy is essential to turn great design and innovation into actual sales. The study implies that tea businesses must move beyond tradition and use modern marketing to reach university students. Practically, companies should focus on digital branding and creative packaging to effectively influence the younger generation's Purchase Decisions.